Les tendances Culturelles dans les Œuvres Romanesques d’Ahmadou Kourouma - SOMANA, Adisa Akinkorede (IJRDO- Journal of Educational Research, 2022)
Cultural tendencies reveal the originality and the reality of the Francophone African literary works vis-à-vis the philosophy, politics, religion, economy and socio-cultural organisation of the peopleof Africa. Ahmadou Kourouma’s literary works have been objet of wide academic discourse, especially in the Francophone world, little attention has, however been accorded the cultural tendencies in his works among the Anglophone researchers. This research, therefore, aims at examining the cultural tendencies such as the character of the praise-singer, la circulation of speech, totemic names, initiations and pleasantry alliances towards an in-depth analysis of their relevance to the development of the works. Sociological theory, which sees author’s work as a reflection of the society is adopted as theoretical framework. Two novels; Les soleils des indépendances as well as Monnè, outrages et défis of Ahmadou Kourouma are purposively selected due to their richness in Malinké culture.